The Legalisation Process of a Qur'?nic Style: The Har?m Months - Fidan Karateke, Aysenur (Ataturk Univ, 2025)
In the history and geography in which the Qur'& amacr;n was revealed, the four forbidden months of Dh & umacr; al-Qa`dah, Dh & umacr; al-Hijjah, Muharram, and Rajab were considered sacred periods by the people. War and all forms of violence were considered forbidden during these times. However, the har & amacr;m months were violated during periods when the interests of the society were jeopardized, and this violation was known as al-nas & imacr;'. Al-nas & imacr;' is the changing of the time of the forbidden months in accordance with human expediency. Thus, the number of months in a cycle becomes thirteen, not twelve. This point is answered in verse 36 of S & umacr;rah al-Tawbah, which states that the number of months in the sight of Allah has been twelve since the creation of the heavens and the earth, and that four of them are forbidden months, and that this is an unchangeable law of Allah. In this study, the contexts of the verses related to the forbidden months are pointed out, and in the example of verse 36 of S & umacr;rah al-Tawbah, the motive by which God takes on an issue that belongs to the worldly and human sphere is analyzed. In this respect, this study is a qualitative research that asks these questions : Did Allah really determine the number of months? Are such matters as dates, clock, calendar, etc., which are purely human elements, really important for a creator? In answering these questions, the hypothetical method was preferred, and textual analysis was used to analyze the verses. The hypothesis of the article is that the information given by the verse about the number of months is a Qur'& amacr;nic style that uses God-centered language in the form of l & amacr;zim f & amacr;'idah al-khabar, and that this style carries what is in the custom to the law. While this is happening, the fact that the verse appears in the form of eternal knowledge is related to the Qur'& amacr;n's God-centered language style.
Keywords: Tafsir; Qur'& amacr;nic style; al-Ahk & amacr;m; al-Ashhur al-Hurum; al-Nas & imacr;'